The Role of Internal Audit and the Implementation of Good Corporate Governance in Fraud Prevention - Adliana, Oshi; Hendratmoko, Anggit Adhiya; Fadjar, Achmad (CENTRAL ASIA AND THE CAUCASUS, 2022)
The background of this research is that there are still many cases of fraud that occur either in the company or in the central/regional government. This study aims to determine whether and how much internal audit and the implementation of GCG play a role in preventing fraud at the West Java Provincial Inspectorate. The independent variable is internal audit and the implementation of GCG, while the dependent variable is fraud prevention. The research method uses the verification method. The research population is internal auditors, totaling 35 people at the Inspectorate of West Java Province. The sampling technique used non-probability sampling technique with saturated sample technique, so the sample amounted to 35 internal auditors at the West Java Provincial Inspectorate. The data analysis method used multiple linear regression analysis. The results of the study show that internal audit and the implementation of GCG have a positive and significant role in preventing fraud. In addition, the role of internal audit and the implementation of GCG in fraud prevention is 48.2%.